The Effectiveness of Duloxetine for Knee Osteoarthritis: An Overview of Systematic Reviews - Zhou, Qinxin; Chen, Jixin; Yu, Weijie; Yang, Kun; Guo, Tianci; Niu, Puyu; Ye, Yuntian; Liu, Aifeng (Frontiers in Physiology, 2022)
Background: Knee osteoarthritis has become a public health problem. Several systematic reviews (SRs) have reported that duloxetine may be an effective way to improve pain and depressive symptoms in patients with KOA. Aim: To evaluate the available results and provide scientific evidence for the efficacy and safety of duloxetine in the treatment of knee osteoarthritis evidence. Methods: Searches were conducted across eight databases starting with the inception and ending on December 31, 2021. The included SRs were assessed respectively by a Measurement Tool to Assess Systematic Reviews (AMSTAR) 2, the Risk of Bias in Systematic Reviews (ROBIS) tool, and the Preferred Reporting Item for Systematic Review and Meta-analysis (PRISMA) statement. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used to assess the quality of the included studies in terms of outcome indicators. Results: A total of six SRs were included in this study. They were generally unsatisfactory in terms of methodological quality, reporting quality, and risk of bias. The limitations were a lack of explaining the reasons for selection, a list of excluded literature, reporting bias assessment, and reporting the potential sources of conflict of interest. According to the GRADE results, limitations were the most commonly downgraded factor, followed by publication bias and inconsistency. Conclusions: Duloxetine may be an effective treatment modality for improving pain and depressive symptoms in KOA with acceptable adverse events. However, due to the low quality of the available evidence, further strengthening of the original study design and improving the quality of evidence from SRs is needed to provide strong, scientific evidence for definitive conclusions.